Targeted SME Financing and Employment Effects : What Do We Know and What Can We Do Differently? - Kumar, Ruchira (World Bank, Washington, DC, 2017)
SME’s form a dominant share of the private sector in developing countries, and account for more than 50 percent of jobs in their respective economies. Besides their positive employment effects, the growth and vibrancy of these firms is also important for broader economic growth, diversification of economic base and as a source of innovation that is exhibited by some of the start-ups. Women-owned SMEs are emerging as one of the fast growing segments within the SME sector. Youth play an important role in the creation of new firms and start up activities. Given this importance of SMEs for creation of more, better and inclusive jobs, there is significant focus on understanding the constraints to growth of this sector and implementing programs to address them in the World Bank Group and the other development institutions. Among the several constraints that they face, access to finance is usually cited as the most important and there are several instruments that can be applied to address this constraint. However, what is the evidence of impact of these programs on the employment effects? This note brings together the learnings and evidence from access to finance interventions on employment and provides some recommendations for development practitioners who seek to maximize this objective from their access to finance interventions.